2021
DOI: 10.3390/min11101087
|View full text |Cite
|
Sign up to set email alerts
|

Potential Uranium Migration within the Geochemical Gradient of the Opalinus Clay System at the Mont Terri

Abstract: Transport properties of potential host rocks for nuclear waste disposal are typically determined in laboratory or in-situ experiments under geochemically controlled and constant conditions. Such a homogeneous assumption is no longer applicable on the host rock scale as can be seen from the pore water profiles of the potential host rock Opalinus Clay at Mont Terri (Switzerland). The embedding aquifers are the hydro-geological boundaries, that established gradients in the 210 m thick low permeable section throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Aqueous uranium speciation in the modelled system is dominated by ternary complexes with carbonate and calcium (Hennig et al, 2020;Hennig and Kühn, 2021a; that are not considered for sorption (Joseph et al, 2013a). Diffusion and sorption experiments of uranium on clay minerals could be modelled without the requirement to include uranium surface complexes with carbonate as they do not sorb or only weakly (Joseph et al, 2013a;Hennig et al, 2020;Hennig and Kühn, 2021b;Tournassat et al, 2018). As ionic strengths in the hydrogeological system of the Opalinus Clay at Mont Terri do not exceed 0.5 mol L −1 (Pearson et al, 2003;Hennig and Kühn, 2021b), the Davies approach (Davies and Shedlovsky, 1964) is used for the database to represent ion-ion interactions (Stockmann et al, 2017;Noseck et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Aqueous uranium speciation in the modelled system is dominated by ternary complexes with carbonate and calcium (Hennig et al, 2020;Hennig and Kühn, 2021a; that are not considered for sorption (Joseph et al, 2013a). Diffusion and sorption experiments of uranium on clay minerals could be modelled without the requirement to include uranium surface complexes with carbonate as they do not sorb or only weakly (Joseph et al, 2013a;Hennig et al, 2020;Hennig and Kühn, 2021b;Tournassat et al, 2018). As ionic strengths in the hydrogeological system of the Opalinus Clay at Mont Terri do not exceed 0.5 mol L −1 (Pearson et al, 2003;Hennig and Kühn, 2021b), the Davies approach (Davies and Shedlovsky, 1964) is used for the database to represent ion-ion interactions (Stockmann et al, 2017;Noseck et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Sorption must be quantified as a function of the geochemical conditions. Further, the results showed that present-day pore water profiles can be explained by diffusive exchange with the embedding aquifers (Mazurek et al, 2011;Hennig and Kühn, 2021b). Previous simulations were conducted using the PSI/Nagra thermodynamic database (Thoenen et al, 2014) including the Nuclear Energy Agency (NEA) data for uranium published by Guillaumont et al (2003).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Montmorillonite fraction, which is a dioctahedral species of the smectite mineral group, can constitute up to 95% of bentonite. ese functional materials provide restriction of groundwater access to radioactive waste, promote conditions for mass transfer between waste and groundwater by diffusion, overwhelm the migration of radionuclides in colloidal form into groundwater, ensure effective sorption after possible depressurization of radioactive waste containers, and so on [40][41][42][43][44][45]. In addition to their presence in the formations housing the storage facilities and their use as backfill material or as sealing material to isolate parts of disposal facility, montmorillonite is also present as a buffer material in the empty space between the package and the host rock [46][47][48].…”
Section: Introductionmentioning
confidence: 99%